From Symbolic Protection to Political Legitimacy: Framing and Institutional Strategy in the Establishment of KemenP2MI - Ikawati, Erina (Universitas Brawijaya, 2025)
This article examines the establishment of the Ministry for the Protection of Indonesian Migrant Workers (KemenP2MI) during the first 100 days of the Prabowo Subianto administration through the lens of Rational Choice Institutionalism (RCI) and framing theory. By analyzing the political calculation behind institutional formation and the communication strategies employed by the government, this study finds that the decision was driven more by short-term legitimacy goals than by a substantive agenda to protect migrant workers. The government's framing presents the ministry as a symbol of state responsiveness and care, particularly through narratives of nationalism and moral obligation. However, implementation challenges suggest a gap between public messaging and institutional capacity. The study argues that while the creation of KemenP2MI may enhance the government's public image, its long-term effectiveness depends on whether symbolic initiatives are matched with structural reform and policy coherence. The findings contribute to broader discussions on policy symbolism, institutional legitimacy, and political communication in contemporary governance.